Inhibition of MicroRNA-494 Reduces Carotid Artery Atherosclerotic Lesion Development and Increases Plaque Stability - Wezel, Anouk; Welten, Sabine M J; Razawy, Wida; Lagraauw, H Maxime; de Vries, Margreet R; Goossens, Eveline A C; Boonstra, Martin C; Hamming, Jaap F; Kandimalla, Ekambar R; Kuiper, Johan; Quax, Paul H A; Nossent, A Yaël; et al. (Annals of surgery, 2015)
Unstable atherosclerotic lesions in carotid arteries require surgical endarterectomy to reduce the risk of ischemic stroke. We aimed to identify microRNAs that exert a broad effect on atherosclerotic plaque formation and stability in the carotid artery. We made a selection of 164 genes involved in atherosclerosis. Using www.targetscan.org, we determined which microRNAs potentially regulate expression of these genes. We identified multiple microRNAs from the 14q32 microRNA cluster, which is highly involved in vascular remodeling. In human plaques, collected during carotid endarterectomy surgery, we found that 14q32 microRNA (miR-494) was abundantly expressed in unstable lesions. We induced atherosclerotic plaque formation in hypercholesterolemic ApoE mice by placing semiconstrictive collars around both carotid arteries. We injected "Gene Silencing Oligonucleotides" against miR-494 (GSO-494) or negative control (GSO-control). Using fluorescently labeled GSOs, we confirmed uptake of GSOs in affected areas of the carotids, but not elsewhere in the vasculature. After injection of GSO-494, we observed significant downregulation of miR-494 expression in the carotid arteries, although miR-494 target genes were upregulated. Further analyses revealed a 65% decrease in plaque size after GSO-494 treatment. Plaque stability was increased in GSO-494-treated mice, determined by an 80% decrease in necrotic core size and a 50% increase in plaque collagen content. Inhibition of miR-494 also resulted in decreased cholesterol levels and decreased very low-density lipoprotein (VLDL) fractions. Treatment with GSO-494 results in smaller atherosclerotic lesions with increased plaque stability. Inhibition of miR-494 may decrease the risk of surgical complications or even avert endarterectomy surgery in some cases.